Implementasi Maximum Power Point Tracker Berbasis Fuzzy Logic Controller dengan Zeta Converter - Afifuddin Rizqi; Sutedjo; Endro Wahjono (Politeknik Aceh, 2021)
Implementation of photovoltaics as a renewable energy source is growing rapidly. The cost of implementing photovoltaic is very high therefore it is necessary to control the optimization of the PV. The V-I aspect of solar cells is nonlinear, changing with the intensity of sunlight and the surface temperature of the photovoltaic, causing the output power of the photovoltaic to vary. This research will use the zeta converter as a DC chooper controlled by MPPT based on fuzzy logic controller. Software Power Simulation (PSIM) is used to simulate MPPT. The MPPT fuzzy logic controller will be compared with the MPPT human psychology optimization (HPO). The simulation results show that MPPT fuzzy gets the same accuracy as MPPT HPO and is better than the average accuracy without MPPT which is 99,98%. Then the speed in finding the maximum MPPT fuzzy point gets a better time tracking when compared to the MPPT HPO which is 0,0283 seconds. MPPT fuzzy is able to exceed the maximum power at varying sunlight intensity and temperature.